"Paper cadavers: the archives of dictatorshio in Guatemala", de Kirsten Weld - Pimentel Chacón, Jonathan (Universidad de Costa Rica, 2016)
Resumen del libro "Paper cadavers: the archives of dictatorshio in Guatemala", de Kirsten Weld